DNA methylation shapes transcription factor binding beyond canonical CpG contexts - Irina Miodownik; Ruben Solozabal; Michael P. O’Hagan; Shira Albeck; Yoav Peleg; Martin Takac; Ariel Afek (Proceedings of the National Academy of Sciences, 2025)
Cytosine methylation is a key epigenetic modification that regulates transcription factor (TF) binding and gene expression. While most current understanding of methylation-sensitive TF binding derives from studies focused exclusively on fully methylated CpG sites, alternative forms—such as non-CpG and hemimethylation—are increasingly recognized as widespread and functionally important, particularly in embryonic stem cells and neurons. However, the direct impact of these alternative methylation contexts on TF–DNA interactions remains poorly defined, largely because current binding assays introduce methylation enzymatically, which precludes strand-specific and position-resolved measurements. Here, we systematically profile the methylation sensitivity of 18 human TFs spanning 11 structural families using chemically synthesized DNA libraries containing position-specific 5-methylcytosines (5mC) in CpG, non-CpG, and hemimethylated contexts, measured via high-throughput protein-binding microarrays. Our results reveal extensive TF sensitivity to methylation state, position, and strand orientation, including strong binding of several TFs to non-CpG and hemimethylated sites. The presence of 5mC can dramatically alter TF–DNA interactions: transforming low-affinity sites into high-affinity ones by enabling new contacts or silencing otherwise favorable motifs through steric hindrance. Genomic analyses further show that the methylation-sensitive sequences identified in vitro are represented within enhancers and regulatory elements, exhibiting distinct methylation patterns across cell types. Together, our findings uncover a previously hidden layer of methylation-dependent TF–DNA recognition, broadening the understanding of epigenetics in transcriptional regulation.